Pengembangan Lembar Kerja Peserta Didik Berbantuan Google Sites pada Materi Getaran, Gelombang, dan Bunyi - Sri Windi Akuba; Tirtawaty Abdjul; Nova Elysia Ntobuo; Citron S. Payu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Advances in technology as a support in terms of developing student worksheets is with the help of the internet. The research objective was to determine the quality (validity, practicality and effectiveness) of Google Sites-assisted student worksheets on Vibration, Waves and Sound material. The research refers to the 4-D Model development research namely Define, Design, Development, and Dissemination. After a limited trial was carried out by 20 class VIII students at SMP Negeri 3 Gorontalo, then an extended trial was carried out by 40 class A-B students at Muhammadiyah Batudaa Middle School. The results obtained from the Google Sites-assisted student worksheets show valid, practical and effective categories.